Formalisation of agricultural research: Activities of the imperial free economic society (second half of the 18th – first half of the 19th centuries) - Holikova, Olena (Linguistics and Culture Review, 2021)
As an independent component of modern research in natural sciences, branch research developed as a result of the accumulation of knowledge from three spheres of public activity – agriculture, branch-specific education, and agricultural research – under the influence of a complex interaction of many external factors. The purpose of this study is to investigate the initial stage of formalization of agricultural research as a branch of natural sciences with the development of corresponding sign-symbolic systems and terminology. Based on the study of printed and archival research of the Imperial Free Economic Society (IFES), adjustments were made to the scientific periodization of the history of research as a branch of knowledge, considering the personalized contribution of its luminaries. Forgotten or little-known studies of pioneers of Ukrainian research – the IFES members: Swiss mathematician L. Euler; Russian scientist of Swedish origin, botanist and chemist E.G. Laxman; a native of Chernihiv Region, Professor of agriculture V. P. Prokopovich, and others were introduced into scientific discourse. The present paper analyses the areas of diverse research activities in agriculture, which were conducted by IFES figures at the early stages of the first scientific and economic association in the Russian Empire.